Low Ankle-Brachial Index Is Associated With Stroke Recurrence in Ischemic Stroke Patients With Atrial Fibrillation - Han, Minho; Baik, Minyoul; Kim, Young Dae; Choi, Junghye; Seo, Kangsik; Park, Eunjeong; Heo, Ji Hoe; Nam, Hyo Suk (Frontiers in Neurology, 2021)
Introduction: Cardioembolic stroke (CE) has poor outcomes and high recurrence rates. A low ankle-brachial index (ABI < 0.9) is associated with atrial fibrillation (AF) and poor stroke outcomes. We investigated whether a low ABI is associated with stroke recurrence, major adverse cardiovascular events (MACE), and mortality in patients with CE and whether this association is affected by AF. Methods: We enrolled patients with CE who underwent ABI measurements during hospitalization. Recurrent stroke was defined based on newly developed neurologic symptoms with relevant lesions seven days after the index stroke. MACE comprised stroke recurrence, myocardial infarction, or death. Results: Of 775 patients, 427 (55.1 %) were AF patients and 348 (44.9 %) were non-AF patients. In total, 194 (25.0 %) patients experienced MACE, including 77 (9.9 %) patients with stroke recurrence and 101 (13.0 %) patients with mortality, during the study period. Multivariable Cox regression analysis showed that an ABI < 0.9 was independently associated with MACE (AF patients: hazard ratio [HR] = 2.327, 95 % confidence interval [CI] = 1.371‒3.949, non-AF patients: HR = 3.116, 95 % CI = 1.465‒6.629) and mortality (AF patients: HR = 2.659, 95 % CI = 1.483‒4.767, non-AF patients: HR = 3.645, 95 % CI = 1.623‒8.187). Stroke recurrence was independently associated with an ABI < 0.9 in AF patients (HR = 3.559, 95 % CI =1 .570‒8.066), but not in non-AF patients (HR = 1.186, 95 % CI = 0.156‒8.989). Conclusions: We found that a low ABI is associated with stroke recurrence, MACE, and mortality in patients with CE. In particular, the association between ABI and recurrent stroke is only present in AF patients. A low ABI may be a useful prognostic marker in patients with CE, especially in AF patients.